IMPLEMENTATION OF THE RADEC MODEL WITH FLIPPED CLASSROOM STRATEGY ASSISTED WITH WORDWALL APPLICATION TO REDUCE MISCONCEPTIONS OF CLASS VII-A STUDENTS UPT SMPN 14 GRESIK - Ikwan Wahyudi; Indra Fardhani; Cahya Nandahwarni (Jurnal Pembelajaran Sains, 2024)
This research aims to reduce students' misconceptions about the Earth and Solar System subject by implementing the RADEC model using a flipped classroom strategy assisted by the Wordwall application. This study is a Classroom Action Research (CAR) that adopts the Kemmis and McTaggart design. The research was conducted in two cycles, each consisting of four components: planning, action, observation, and reflection. The study was conducted in Class VII-A of UPT SMPN 14 Gresik, which consisted of 30 students. Data was collected through classroom observations, student reflections, and a four-tier diagnostic test. Data analysis was performed using qualitative descriptive analysis to describe changes in student misconceptions. The results of the first cycle showed that students' conceptions of the Earth and the Solar System were as follows: 60.33% had scientific conceptions, 16.33% lacked knowledge, and 23.33% had misconceptions. The results of the second cycle showed an improvement in students' scientific conceptions and a decrease in the lack of knowledge and misconceptions: 86.67% had scientific conceptions, 4.33% lacked knowledge, and 9.00% had misconceptions. It can be concluded that implementing the RADEC model with a flipped classroom strategy assisted by the Wordwall application can be an alternative solution to reduce students' misconceptions in science learning, especially Earth and the Solar System.